Sintesis Dan Karakterisasi Nanopartikel Fe3o4/Tio2-Co Dengan Variasi Suhu Kalsinasi Dalam Mendegradasi Methylene Blue - Lubis, Hilwa Salsabila; Lubis, Ridwan Yusuf; Daulay, Abdul Halim (Fakultas Teknik UMSU, 2025)
A study has been conducted on the effect of calcination temperature on the characteristics of Fe3O4/TiO2-Co nanoparticles for the degradation of Methylene Blue. The nanoparticles were synthesized using the coprecipitation method. The aim of this research was to investigate the influence of calcination temperature on the morphological structure, crystal size, and degradation percentage of Methylene Blue, with variations in calcination temperatures of 400, 500, and 600 °C. The samples were characterized using Scanning Electron Microscope (SEM), X-ray diffractometer (XRD), and UV-Vis Spectrophotometer. The SEM results indicated that at a calcination temperature of 400 °C, agglomeration still occurred. The XRD analysis showed that as the calcination temperature increased, the crystal size decreased, with the sizes for FTC400, FTC500, and FTC600 samples being 30.53 nm, 30.13 nm, and 28.74 nm, respectively. The UV-Vis test results revealed that the higher the calcination temperature, the higher the degradation percentage, reaching 99.40% for the FTC600 sample